The Representation of Riau Malay Traditional Music in the SUNO AI Application: A Post-Reality Perspective - Ridho Fatwandi; Daryusti Daryusti (Gondang: Jurnal Seni dan Budaya, 2026)
This research aims to examine how traditional Malay music is represented through the Suno AI application and to understand this phenomenon using Jean Baudrillard’s post-reality perspective. The study employs a descriptive qualitative approach with digital experimentation techniques and in-depth interviews. Data were obtained from AI-generated Malay music (zapin, joget, and langgam), which was then compared to original traditional music, supported by the views of informants with expertise in Malay music. The findings indicate that AI is capable of presenting musical similarities at the surface level, such as rhythm, tempo, and the distinctive Malay nuance. However, the music produced tends to lose essential elements such as feeling, spontaneity, social interaction, and cultural meaning. From the post-reality perspective, this condition shows that AI music has entered the stage of simulation and simulacra, where culture is represented as sound signs detached from its original reality. Moreover, AI music can create hyperreality, a form of culture that appears neater and more perfect, but lacks depth of meaning. The presence of AI is not as an agent that changes the way culture is understood and represented in the digital era. AI-generated Malay music becomes a cultural representation that is simulational and has the potential to shift society’s understanding of the authenticity of traditional culture.